PRODUCTS OF MULTIPLICATION, COMPOSITION AND DIFFERENTIATION OPERATORS FROM MIXED-NORM SPACES TO WEIGHTED-TYPE SPACES - Zhang, Fang; Liu, Yongmin (Taiwanese journal of mathematics, 2014)
Letφbe an analytic self-map of the unit disk 𝔻,H(𝔻) the space of analytic functions on 𝔻 andψ 1,ψ 2∈H(𝔻). Recently Stević and co-workers defined the following operator T ψ 1 , ψ 2 , φ f ( z ) = ψ 1 ( z ) f ( φ ( z ) ) + ψ 2 ( z ) f ′ ( φ ( z ) ) ,